2006
DOI: 10.1103/physreve.73.031608
|View full text |Cite
|
Sign up to set email alerts
|

Breath figure templated self-assembly of porous diblock copolymer films

Abstract: Porous polyethylene oxide-b-polyfluorooctylmethacrylate (PEO-b-PFOMA) diblock copolymer films were drop cast onto substrates from Freon (1,1,2-trichlorotrifluoroethane) in a humid atmosphere. The pores in the films exhibit long range hexagonal order in some cases, depending on the PFOMA-to-PEO molecular weight ratio. Films with the best ordered pores were formed with PFOMA-to-PEO ratios of 70 kDa:2 kDa. The pores in the polymer films derive from water droplets that condense as Freon evaporates. The polymer sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 41 publications
1
60
1
Order By: Relevance
“…The other possible mechanism could be analogous to the widely observed breath figure (BF) formation on drop-cast polymer films. [62][63][64][65][66][67][68][69][70][71][72] In earlier publications, 41,42 we proposed the possibility that water condensation onto the PEO-based block copolymers leads to PEO domain ordering. After solvent annealing, the solvent evaporation causes the cooling of the film surface.…”
Section: Discussionmentioning
confidence: 99%
“…The other possible mechanism could be analogous to the widely observed breath figure (BF) formation on drop-cast polymer films. [62][63][64][65][66][67][68][69][70][71][72] In earlier publications, 41,42 we proposed the possibility that water condensation onto the PEO-based block copolymers leads to PEO domain ordering. After solvent annealing, the solvent evaporation causes the cooling of the film surface.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the fabricated pores is easily controllable by adjusting various processing parameters such as the polymer concentration, [31] molecular weight or chemical structure of used polymer, [32][33][34][35] humidity or flow rate of applied air stream, [36] solvent evaporation rate, [37] solution casting temperature, [38] film thickness, [39] etc. Encapsulation of aqueous droplets by a thin polymer stratum induced by thermocapillary or Marangoni convection has been suggested as a mechanism for a hard colloid-like interaction between aqueous droplets without the use of colloid stabilizer.…”
Section: Full Papermentioning
confidence: 99%
“…Nucleation of aqueous droplets is known to be promoted in a polymer solution containing a hydrophilic polymer component. [32] However, the overall condensation rate of the aqueous droplets does not significantly depend on the chemical nature of the dissolved polymer. As a result, pore size decreases with the content of hydrophilic component.…”
Section: Full Papermentioning
confidence: 99%
“…An increase in the nucleation density leads to smaller final droplet size and this is a promising way to produce porous films having various pore sizes and spacing. 223 Liu and coworkers produced fluorescent honeycomb-patterned films of amphiphilic hyperbranched poly(amidoamine)s with high reproducibility on variety of substrates in a wide range of humidities. They reported that the patterned film thicknesses can be changed from nanometer to micrometer scale by altering the polymer concentration.…”
mentioning
confidence: 99%